"Thousands of lives and millions of rubles!" The Russo-Turkish War of 1877-1878 reflected in Czech periodicals - Kouba, Miroslav (My University, 2024)
The years 1876–1878 were a time when the nationalist movement of the southern Slavic nations in the Balkans was culminating, especially among the Bulgarians, who under the influence of the anti-Turkish rebellion in Herzegovina in 1875 accelerated preparations for similarly organized rebel activities. These events showed the Bulgarian issue as being not as an internal affair of the Ottoman Empire, but rather as being integral to the Great Eastern Crisis, related to differing opinions of European powers, especially Great Britain and Russia, which was also followed closely by the Czech periodical press (e.g. Národní listy, Světozor, Čech, etc.). This study examines the main spectrum of attitudes taken on these questions of international politics by Czech journalists, especially those working for Národní listy, the leading Czech periodical of that era, who during this era of culminating Czech emancipation were finally coming of age in the sense of an independent profession. The focus will not be the ideological parameters of the Russo-Turkish War, but rather the perception of the military conflict and its reflections in a geographically relatively remote environment, which continue to be relevant even now.
"Tisíce životů a miliony rublů!" Odraz rusko-turecké války 1877-1878 v českém tisku
Keywords: Russo-Turkish War of 1877-1878; Czech periodical press; Národní listy; Bulgaria; National movement; Historical memory; rusko-turecká válka 1877-1878; český periodický tisk; Národní listy; Bulharsko; národní hnutí; historická paměť